DESAIN KONSEP PURWARUPA MESIN INJECTION MOLDING TIPE VERTIKAL UNTUK DAUR ULANG LIMBAH PLASTIK SKALA RUMAH TANGGA - Sufiyanto, Sufiyanto; Niam, Waridin; Marfizal, Marfizal; Aziz, Myson (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
Plastic waste is the main cause of environmental pollution. It is necessary to research the design of the Injection Molding machine to process plastic waste. This study describes the design concept of a vertical type Injection Molding machine prototype by considering the factors to be utilized by small-scale plastic recycling businesses. The design stage starts from the identification of component requirements to the design of 3D drawings. The results of this study obtained a prototype design of a Vertical Injection Molding Machine. The embodiment of the design is not only determined directly by the design team and the manufacturing team, but is obtained from customer requests described in the technical specifications. At the concept design stage, there are 5 sub-functions and each function has 3 to 4 options. From the combination of these sub-functions and options, 3 assembly sketches were obtained so that 3 alternative design concepts were obtained. From the results of the concept assessment, design concept C was chosen from several alternative concepts.